Kegiatan Branding Sebagai Strategi Pemasaran Dan Pengembangan UMKM Madona Kulit - Nurul Azizah; Moch Rizky Ramadhan (STIPAS Tahasak Danum Pambelum Keuskupan Palangkaraya, 2023)
Indonesia may be a nation wealthy in characteristic assets. This tremendous riches is well overseen by Indonesian industry, coming about in a wide assortment of items. As you know, not as it were the industry, Umbakes has moreover contributed to different prepared items through innovation and special creation. One of the most places his MKKNT-MBKM understudies work within the Krampock area of the city of Blitar, he has issues with item improvement and showcasing variables. The reason of this committed movement is hence to arrange your promoting methodology with the fundamental exertion. The strategies utilized are subjective and incorporate sorts of information collection through perception, interviews and documentation of action at umkm. As a result of this devotion, umkm's items have been able to reach a well-developed and reasonable side of the market.